Employing Strategic Thinking in South American 4icrofinance Institutions - CONCARI, GUSTAVO (Revista Iberoamericana de Estudios de Desarrollo)
The article is about the use of strategic thinking in microfinance in South America. Microfinance is an important business in South America today, its importance lies in its ability to transform poor people and informal enterprises into citizens and formal companies making human beings grow as individuals at the same time. The sector is very strong in the region despite its youth and maybe it's time to use the ideas of business strategy developed for traditional businesses. The goal of this paper is then to use the ideas of business strategy in microfinance. A classic strategy scheme called the Ansoff matrix is used for this. It proposes two axes (product and market) as possible ways for developing a business. The work includes the theoretical development of this scheme and evaluations from experts interviewed to give their opinion on it, evaluations that make the idea richer while pointing the possible weaknesses of the model